1999
DOI: 10.1902/jop.1999.70.9.1085
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Soft Tissue Closure Following Guided Bone Regeneration: Technical Considerations and Report of 723 Cases

Abstract: The purpose of this paper is to present simple clinical techniques which have been utilized in a significant number of consecutive cases to maintain primary closure throughout the course of regeneration. The maintenance of soft tissue primary closure following guided bone regeneration (GBR) therapy, while considered a considerable challenge, is recognized as contributing to the maximization of therapeutic results. A retrospective analysis of the maintenance of such soft tissue primary closure following the uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 10 publications
0
42
0
6
Order By: Relevance
“…Furthermore, it has been demonstrated consistently that the grafted site for GBR may be completely separated and protected from the external environment by the periosteum [4]. It has been indicated that using periosteal flaps as the primary closure for graft materials can promote both wound healing and the creation of new bone [5].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated consistently that the grafted site for GBR may be completely separated and protected from the external environment by the periosteum [4]. It has been indicated that using periosteal flaps as the primary closure for graft materials can promote both wound healing and the creation of new bone [5].…”
Section: Introductionmentioning
confidence: 99%
“…53,54 Although bone regeneration can be achieved without attaining and maintaining passive soft tissue primary closure over the regenerating site, the extent and morphology of the regenerated hard tissues often fall short of the desired ideal treatment outcome. In addition, the resultant soft tissue covering when passive soft tissue primary closure is not maintained is usually thinner than desired and represents a potential aesthetic compromise.…”
Section: Technical Complicationsmentioning
confidence: 99%
“…In contemporary implant treatment, the necessity of guided bone regeneration (GBR) has increased due to the concept of contour augmentation, and frequent GBR procedures usually lead to the reduction of keratinized mucosa around implants, since the flaps have to be advanced for tensionless primary closure [56]. To correct these mucogingival issues, a free gingival graft (FGG), an apically positioned flap, or a connective tissue graft is required if there is a minimal width of keratinized tissue, in order to increase the width [7].…”
Section: Introductionmentioning
confidence: 99%